2020
DOI: 10.3390/cancers12040805
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the MicroRNAs and Microbiota in Cancer Development: Roles and Therapeutic Opportunities

Abstract: The human microbiota is made up of the fungi, bacteria, protozoa and viruses cohabiting within the human body. An altered microbiota can provoke diseases such as cancer. The mechanisms by which a modified microbiota can intervene in the onset and progression of neoplastic diseases are manifold. For instance, these include the effects on the immune system and the onset of obesity. A different mechanism seems to be constituted by the continuous and bidirectional relationships existing between microbiota and miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 93 publications
(103 reference statements)
1
41
0
Order By: Relevance
“…In humans, about 1.5 kg microbes reside in the gut and make up half of the fecal matter biomass [ 120 ]. Increasing evidence indicated that gut microbiota is considered as a potential factor in the pathogenesis of obesity and associated metabolic disorders, even cancers [ 121 , 122 , 123 ]. Understanding the role of gut microbiome in obese and CRC individuals will provide potential molecular insights and therapeutic targets to prevent or treat both diseases.…”
Section: The Mechanistic Insights Linking Obesity With Crcmentioning
confidence: 99%
“…In humans, about 1.5 kg microbes reside in the gut and make up half of the fecal matter biomass [ 120 ]. Increasing evidence indicated that gut microbiota is considered as a potential factor in the pathogenesis of obesity and associated metabolic disorders, even cancers [ 121 , 122 , 123 ]. Understanding the role of gut microbiome in obese and CRC individuals will provide potential molecular insights and therapeutic targets to prevent or treat both diseases.…”
Section: The Mechanistic Insights Linking Obesity With Crcmentioning
confidence: 99%
“…Immunotherapy (briefly mentioned in this review) and modulation of the function of various non-coding RNAs are other forms of cancer therapies that we did not have time to address here [609][610][611][612][613][614].…”
Section: Discussionmentioning
confidence: 99%
“…Other therapeutic approaches have been attempted. Recently, mounting proof has demonstrated that variation in the expression of microRNAs (miRNAs) can control essential procedures in HSPCs, such as growth, differentiation, inflammation, and tumor evolution [125][126][127][128].…”
Section: Targeting the Inflammatory Microenvironmentmentioning
confidence: 99%